Kolerasi antara Pemahaman Diri terhadap Kesehatan Mental Siswa dalam Pendidikan - Habsy, Bakhrudin All; Maharani, Meutya Faiha Adila; Fasa, Redita Amalia; Rusty, Fisya Aulia (TSAQOFAH, 2024)
Education plays an important role in the formation of strong human resources that can compete both domestically and at the international level. A mentally healthy person demonstrates the ability to exercise restraint, show intelligence, and behave with consideration for the feelings of others. The importance of mental education is discussed in this article. The purpose of this article is to understand what educational psychology is and how mental health plays a role in education. Collecting literature data, reading and taking notes, and managing literature sources are all methods of literature study research used in this article. Everyone should make an effort to recognize themselves, which is very important so that they can identify their strengths and weaknesses. Rational emotive therapy helps individuals to get out of illogical ideas and learn logical or realistic ideas.